Community Education, Tradition, and the Reconfiguration of Village Governance among Ethnic Minorities in Vietnam’s Central Highlands - Minh, Đức (Technium Social Sciences Journal, 2026)
This paper studies community education and tradition in the sustenance and development of ethnic minority groups in the Central Highlands of Vietnam. The study, through a mixed-method approach, states that community education is more than an avenue for the communication of knowledge; rather, it is a tool of social governance that sustains a community’s cultural patrimony and collective identity. Rather than disappearing, tradition as a social phenomenon, under the impact of modernization, changes through adaptation and selective retention. The study also demonstrates that the interaction of education and tradition is foundational to social integration and the governance of villages. The paper further assesses the impacts of state and NGO cultural interventions, in the face of globalization and economic development, and their effects on enculturation. The study, as a whole, underscores the need for a policy encompassing the three integrated components of education, culture, and economic development, specifically targeting ethnic minority groups.